2011
DOI: 10.1007/s11010-011-0734-4
|View full text |Cite
|
Sign up to set email alerts
|

The melanoma-associated antigen-A3, -A4 genes: relation to the risk and clinicopathological parameters in breast cancer patients

Abstract: This study aimed to evaluate the clinical reliability and accuracy of two MAGE transcripts (MAGE-A3, MAGE-A4 mRNA) in the peripheral blood (PB) of patients with breast cancer (BC), and to evaluate their potential limits and utility to detect BC. We aimed also to analyze their relation to clinicopathological characteristics of the tumor. This study is a prospective, controlled, double-blinded study conducted on 100 BC women and 100 age-matched control women. There were 52 patients with localized breast mass wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Furthermore MAGE-A proteins may reduce malignant potential by inhibiting the tumor suppressor p53 (9, 24). Finally, MAGE is expressed in a variety of malignancies (2527), opening the possibility of extending this immunotherapeutic strategy to other hematological malignancies and tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore MAGE-A proteins may reduce malignant potential by inhibiting the tumor suppressor p53 (9, 24). Finally, MAGE is expressed in a variety of malignancies (2527), opening the possibility of extending this immunotherapeutic strategy to other hematological malignancies and tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-one cancer/testis antigens (8%) and 119 testis proteins (11 testis-specific proteins) were included in the breast cancer protein profiles and these proteins warrant further study. Among these proteins, a recent study showed that MAGE-A3 and A4 in the peripheral blood of breast cancer patients may have potential prognostic and predictive implications (44). All of these proteins are promising specific tumor markers of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Ayyoub et al (16) reported that MAGEA3 and MAGEA6 expression in primary breast cancer is associated with hormone receptor-negative status, high histological grade and poor survival. Cabezón et al (17) indicated that MAGEA3 and MAGEA4 may be associated with risk and the clinicopathological parameters of breast cancer (17,18). In breast cancer, MAGEA9-A11 have been identified as being associated with poor prognosis (1923).…”
Section: Introductionmentioning
confidence: 99%